Neonatal diabetes mellitus in developing country: A rare case report - Najati, Fika Amalia; Rochmah, Nur; Hisbiyah, Yuni; Perwitasari, Rayi Kurnia; Faizi, Muhammad (Edelweiss Applied Science and Technology, 2025)
Neonatal Diabetes Mellitus (NDM) is a rare monogenic form of diabetes characterized by persistent hyperglycemia within the first six months of life. Managing NDM presents significant challenges due to variations in insulin sensitivity and glycemic fluctuations. This report aims to elucidate the diagnostic difficulties and therapeutic strategies in resource-limited settings. A two-month-old male infant presented with respiratory distress, fever, and productive cough, accompanied by Kussmaul respiration. Laboratory investigations revealed a random blood glucose level of 637 mg/dL, +3 urine ketones, and an HbA1c of 9.4%, consistent with diabetic ketoacidosis (DKA). Considering his age and clinical presentation, NDM was suspected. Continuous intravenous insulin infusion resulted in marked glycemic fluctuations, with glucose levels ranging from less than 100 mg/dL to 550 mg/dL. A C-peptide stimulation test performed after administering glibenclamide showed an increase from 0.7 to 2.2 ng/mL, indicating preserved β-cell function. Respiratory distress combined with persistent hyperglycemia in infants may suggest DKA. Transitioning from insulin to sulfonylurea therapy, guided by C-peptide testing, highlights the importance of early diagnosis of NDM and personalized treatment approaches to optimize metabolic control. Early recognition of NDM in infants with persistent hyperglycemia and appropriate sulfonylurea therapy can simplify management and improve long-term outcomes, especially in resource-limited settings.